The time of Stalin : portrait of a tyranny - Antonov-Ovseenko, Anton, 1920-2013 (New York : Harper & Row, 1981)
'Anton Antonov-Ovseyenko is truly a child of the Bolshevik Revolution (and its traumatic outcome). His father, Vladimir Antonov-Ovseyenko, led the Bolshevik storming of the Winter Palace in October 1917 and went on to become a famous Soviet military leader, political figure, diplomat. He was finally killed in Stalin's purge of the late thirties (...) Now his son, Anton Antonov-Ovseyenko, almost totally blind and a survivor of many years in Stalin's prisons and concentration camps. tells the story of Stalin from personal experience (...) A professional historian since he was freed in the 1950s, the author has made use of family connections and other special circumstances to get access to previously unknown sources--some obviously high-ranking--and to personal testimonies on his subject. He has unearthed a wealth of new and startling information about Stalin and his long. despotic rule--Stalin's rise to dictatorship, hos private life, his brutal assault on the peasants during collectivization, his plotting of the Kirov assassination, the great terror of the 1930s,the actual number of his millions of victims, the catastrophic pact with Hitler and subsequent failure to prepare for the German invasionin 1941, his last years as a virtual god, and, finally, his bizarre death'--publisher
'First published in the Russian language in the United States by Chekhov Publishing Corporation'.
Includes bibliographical notes and index, p. 357-374.
HU OSA 300 - RFE/RL collection
Donation of Anatole Shub
Keywords: Stalin, Joseph, -- 1879-1953.; Heads of state -- Soviet Union -- Biography